Food transfers, cash transfers, behavior change communication and child nutrition: Evidence from Bangladesh - Ahmed, Akhter; Hoddinott, John F.; Roy, Shalini (Oxford University Press, 2025)
This paper reports the results of two 2-year randomized control trials in two poor rural areas of Bangladesh. Treatment arms included monthly cash transfers, monthly food rations of equivalent value to the cash transfers, and mixed monthly cash and food transfers, and treatment arms—one with food and one with cash—that combined transfers with nutrition-behavior communication change (BCC). This design enables a comparison of transfer modalities within the same experiment. Intent-to-treat estimators show that cash transfers and nutrition BCC had a large impact on nutritional status, a 0.25 standard deviation increase in height-for-age z-scores and a 7.8 percentage point decrease in stunting prevalence. No other treatment arm affected anthropometric outcomes. Mechanisms underlying these impacts are explored. Improved diets—particularly increased intake of animal source foods in the cash plus BCC arm—are consistent with the improvements observed in this paper.